2019
DOI: 10.1080/02670836.2019.1613801
|View full text |Cite
|
Sign up to set email alerts
|

Friction Hydro-Pillar Processing and Tungsten Inert Gas Welding of a Duplex Stainless Steel

Abstract: This work presents friction hydro-pillar processing (FHPP) and tungsten inert gas (TIG) welding of SAF2205 duplex stainless steel. Weld microstructural and mechanical characterisation were carried out based on the standards (DNV-RP-F112 and DNV-OS-F101). Therefore, optical microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction were used. In addition, mechanical properties were evaluated by microhardness measurements. Furthermore, the joining processes were thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sugimoto et al [9] reported that FSW of DSS 2205 could retain the original substrate properties. FTSW of DSS parts is found promising for line-pipe [10] and, marine and underwater [11] applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugimoto et al [9] reported that FSW of DSS 2205 could retain the original substrate properties. FTSW of DSS parts is found promising for line-pipe [10] and, marine and underwater [11] applications.…”
Section: Introductionmentioning
confidence: 99%
“…FTSW has evolved from a similar solid-state technique friction hydro-pillar processing (FHPP), which is limited to a single insert. Meinhardt et al [11] and Lessa et al [10] used FHPP for DSS 2205 and found joints with acceptable mechanical and corrosion properties. Kanan et al [12] and Landell et al [13] reported a fairly homogenous joint structure for FHPP for high carbon steel substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, attempts to quantify the influence of the intermetallic phases on the joint properties are not reported in detail. For instance, Lessa et al 9 studied the friction hydro-pillar processing (FHPP) of DSS 2205 to repair the discontinuities commonly observed in offshore structures, and oil and gas pipelines. The authors could restrict the formation of brittle intermetallic phases within the permissible limits for offshore structures (DNV-RP-F112).…”
Section: Introductionmentioning
confidence: 99%
“…FTSW has evolved from a similar solid-state technique FHPP, which is limited to a single insert. Meinhardt et al 10 and Lessa et al 9 used FHPP for DSS 2205 and found welded joints with acceptable mechanical and corrosion properties. Kanan et al 11 and Landell et al 12 reported a fairly homogenous joint structure for FHPP of high carbon steel substrates.…”
Section: Introductionmentioning
confidence: 99%